Utilization of Stacko Block as a Career Counseling Media in Schools - Rindiyani, Dwi; Handoyo, Alfiandy Warih; Prabowo, Arga Satrio (Konseling Edukasi : Journal of Guidance and Counseling, 2024)
Utilization of Stacko Block as a Career Counseling Media in Schools. This study aims to see the effectiveness of implementing Stacko Holland media in improving career insights. The research method used in this research is nonequivalent control group design quasi-experimental. The research subjects in this study were students of class XI SMAN 1 Baros. There were 20 students who became research participants who were divided into two groups, namely the experimental group and the control group. Data collection techniques used include structured interviews and Holland's career insight questionnaire. The data analysis technique used in this research is descriptive statistical analysis and Mann-Whitney U hypothesis test analysis. Based on the results of the Mann-Whitney U hypothesis test analysis, the Asymp. Sig (2-tailed) value of 0.00 with a significance level of 0.05. The calculation results show that the hypothesis test shows that Asymp. Sig (2-tailed) < 0.05, from this it can be concluded that the implementation of Stacko Holland game media is effective and able to significantly improve the career insights of class XI students of SMAN 1 Baros.Keywords: Utilization, Stacko Block, Career Counseling